The Racoon Eye Sign in the Investigation of Dementia Using 18F-Florbetaben. (May 2019) - Ordidge, Katherine; Gandy, Nemi; Arshad, Mubarik; Win, Zarni
Abstract : Abstract: Differentiating Alzheimer disease (AD) from other forms of cognitive impairment and from normal aging can be challenging. As a consequence, the diagnosis of AD can be delayed, often occurring too late for meaningful intervention. The role of β-amyloid plaques in the pathogenesis of AD provides a target for highly sensitive and specific image quantification of amyloid plaque burden using β-amyloid PET ( 18 F-florbetaben). Here we present the case of a 77-year-old woman with increasing memory impairment and striking white matter changes on MRI, with the "racoon eye" sign on 18 F-florebetaben PET imaging.